Expression of aldehyde dehydrogenase 1 as a marker of mammary stem cells in benign and malignant breast lesions of Ghanaian women. Issue 3 (28th August 2012) - Schwartz, Theresa; Stark, Azadeh; Pang, Judy; Awuah, Baffour; Kleer, Celina G.; Quayson, Solomon; Kingman, Stephanie; Aitpillah, Francis; Abantanga, Francis; Jiagge, Evelyn; Oppong, Joseph K.; Osei‐Bonsu, Ernest; et al.
Abstract BACKGROUND: Breast cancers that are negative for the estrogen receptor (ER), the progesterone receptor (PR), and the HER2 (human epidermal growth factor receptor 2) marker are more prevalent among African women, and the biologically aggressive nature of these triple‐negative breast cancers (TNBCs) may be attributed to their mammary stem cell features. Little is known about expression of the mammary stem cell marker aldehyde dehydrogenase 1 (ALDH1) in African women. Novel data are reported regarding ALDH1 expression in benign and cancerous breast tissue of Ghanaian women. METHODS: Formalin‐fixed, paraffin‐embedded specimens were transported from the Komfo Anoyke Teaching Hospital in Kumasi, Ghana to the University of Michigan for centralized histopathology study. Expression of ER, PR, HER2, and ALDH1 was assessed by immunohistochemistry. ALDH1 staining was further characterized by its presence in stromal versus epithelial and/or tumor components of tissue. RESULTS: A total of 173 women contributed to this study: 69 with benign breast conditions, mean age 24 years, and 104 with breast cancer, mean age 49 years. The proportion of benign breast conditions expressing stromal ALDH1 (n = 40, 58%) was significantly higher than those with cancer (n = 44, 42.3%) (P = .043). Among the cancers, TNBC had the highest prevalence of ALDH1 expression, either in stroma or in epithelial cells. More than 2‐fold higher likelihood of ALDH1 expression was observed in TNBC cases compared with other breast cancer subtypes (odds ratio = 2.38, 95% confidence interval 1.03‐5.52, P = .042). CONCLUSIONS: ALDH1 expression was higher in stromal components of benign compared with cancerous lesions. Of the ER‐, PR‐, and HER2‐defined subtypes of breast cancer, expression of ALDH1 was highest in TNBC. Cancer 2013. © 2012 American Cancer Society.